Empirical-Triangulation Model of the Effectiveness of Judicial Practice - Vasyliev, Sergii (Problems of legality, 2026)
The relevance of the study is determined by the need to develop scientifically sound approaches to assessing the effectiveness of judicial practice in the context of the transformation of the judicial system, the complication of law enforcement processes, and the growing role of empirical methods in modern jurisprudence. Formal legal and normative-dogmatic approaches do not fully reflect the real results of judicial practice, which limits the possibilities for objective analysis of its impact on legal relations and the behavior of participants in judicial proceedings. The purpose of the article is to provide a theoretical justification and empirical verification of the empirical-triangulation model of the effectiveness of judicial practice, as well as to develop comprehensive approaches to its scientific evaluation. The methodological basis of the study is a combination of analysis of judicial practice, observation, socio-legal surveys, and content analysis of court decisions, which allows for a multidimensional study of law enforcement processes and mutual verification of the results obtained. As a result of the study, the distinction between the effectiveness of justice and the effectiveness of judicial practice as interrelated but not identical legal phenomena is substantiated; judicial practice is defined as an independent object of scientific analysis; the content of its theoretical and actual effectiveness is revealed. The limitations of traditional normative-dogmatic approaches have been proven, and the expediency of systematically using empirical data to identify trends in law enforcement, typical problems, and latent dysfunctions in judicial activity has been substantiated. An empirical triangulation model of judicial practice effectiveness has been proposed as a comprehensive system of scientific knowledge that combines normative-projective, procedural-resultative, and socio-communicative empirical data and provides a comprehensive assessment of the ability of judicial practice to achieve the goals of justice. Prospects for further research are related to the testing of the proposed model for specific categories of cases, the expansion of the empirical base, and the use of the results obtained to improve judicial practice and shape judicial policy.